Urinary Complications Among Patients With Anorectal Malformation Seen At Gezira National Center Of Pediatric Surgery-Sudan - Yagoub, Adam; Nugud, Faisal (مجلة الجزيرة للعلوم الصحية; مجلد 16 عدد 1 (2020), 2020)
Background: Anorectal malformation (ARM) is a spectrum of structural congenital defects involving the anorectum and variable segments of the urogenital system in boys and girls, incidence occurs in 1 in 5000 births, The malformations range from skin level defects such as rectoperineal fistulas to complex lesions such as persistent cloaca. Urological anomalies are frequently seen in patients with anorectal malformations and can result in upper urinary tract deterioration. Patients and methods: This study is a retrospective, descriptive, cross-secional hospital based study Conducted at Gezira national center for pediatric surgery in Sudan, from february2016 to Jan 2018, The study sample included (93 cases). the study was conducted in patients with anorectal malformation, data was collected using a questionnaire, data was analyzed using SPSS version 20. Results: A total of 93 ARM patients where studied, 49 males and 44 females, overall urinary anomalies were 31.2% in patients of anorectal malformation, vesicoureteric reflux 12.9% was most common urinary anomaly only one  needed surgery. hydronephrosis 10.8%, polycystic kidney 4.3%, solitary kidney 3.2% .the most common urinary complications  recurrent urinary tract infection 18.3%, stone formation 8.6%, urinary incontinence 6.5%, urethral stricture 3.2%. Conclusion: Urinary anomalies in patients with complex ARM are more severe than in patients with less complex ARM. Ultrasonography of the urinary tract should be performed in all patients. Voiding cystourethrography can be reserved for patients with dilated upper urinary tracts, urinary tract infections or lumbosacral and spinal abnormalities. All patients with complex ARM need urodynamic investigations. When using these indications, the screening for urological anomalies in ARM patients can be optimized with long-term follow-up in selected patients.